ANALISIS KOMPARTEMEN DESAIN TAS PERLENGKAPAN KAMERA UNTUK VIDEO BLOGGER - Syifa Madani; Yanuar Herlambang; Terbit Setya Pambudi (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2022)
Increasing video content on social media has led to more people doing video blogging or referred as video bloggers (vloggers). It affects the number of vloggers in Indonesia, reaching half the total number in the world. Vloggers need a bag to carry equipment so that the equipment is stored correctly and undamaged when creating content outdoors. The specific bags for camera equipment on the market still do not fulfill their requirement. These conditions require vloggers to provide various bags, while vlogger activities and equipment always change according to content needs. This study aims to answer the problems experienced by vloggers by increasing the effectiveness of the bag through concepts, systems, access, and compartment layouts. The method used in developing the compartment starts from collecting data such as questionnaires and interviews to identify problems, observation of existing products and product references, activities studies, continued analysis data, design concepts to production, and product testing.